DETECTION OF PANTON-VALENTINE LEUKOCIDIN (PVL) GENE AGAINST METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) IN DIABETIC ULCER PATIENTS - Prisma Anjarlena; Suliati; Wisnu Istanto; Retno Sasongkowati (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Diabetes Mellitus (DM) patients are susceptible to wound infections brought on by S. aureus bacteria, in dealing with infections caused by bacteria, antibiotic treatment was conducted. Nevertheless, misapplication of antibiotics might lead to drug resistance or MRSA. Panton-Valentine Leukocidin (PVL) is a crucial factor of S. aureus pathogenicity. Skin and soft tissue infections can be caused by the PVL gene. Purpose: To detect PVL gene in ulcer swabs of diabetic mellitus patients against MRSA strains. Method: Employing descriptive quantitative data analysis of PVL gene detection observations on ulcer swab of diabetes mellitus patients using the RT-PCR method. Ulcer swab samples were collected at Dharmahusada and Banyu Urip Diabetes Wound Specialist Hospital, Surabaya, East Java, Indonesia. The research was conducted at the Department of Medical Laboratory Technology, Health Polytechnic Ministry of Health Surabaya, Bacteriology Laboratory for the isolation and identification of MRSA and Molecular Biology Laboratory for the detection of the PVL gene in April–May 2022. Result: From 30 samples of ulcer swabs, 8 samples were positive for MRSA and 22 samples were negative for MRSA. After that, the MRSA positive samples were detected using the RT-PCR method to detect the PVL gene. The results of PVL detection were obtained from 6 samples (75%) positive for detecting the PVL gene and 2 samples (25%) negative for detecting the PVL gene. Conclusion: The results of the study showed that ulcer swabs from diabetes mellitus patients had the PVL gene against MRSA.